PENGARUH PENERAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE TERHADAP CIVIC DISPOSITION SISWA KELAS XI SMA NEGERI 1 TERAS BOYOLALI TAHUN AJARAN 2016/2017 - Nur Aini; Winarno Winarno; Muhammad Hendri Nuryadi (PKn Progresif : Jurnal Pemikiran dan Penelitian Kewarganegaraan, 2018)
The objective of research was to find out whether or not there is an effect of value clarification technique learning model application on civic disposition in the 11th graders of SMA Negeri 1 Teras Boyolali in the school year of 2016/2017. This study was an experimental quantitative research. The research design was true experimental design with posttest only control design model. The population of research was the 11th graders of SMA Negeri 1 Teras Boyolali in the school year of 2016/2017. The sampling technique used was cluster random sampling. The sample of research consisted of 68 students: 34 in experimental and 34 in control groups. Data collection in this research was carried out using observation and questionnaire. Data validation for the students’ civic disposition questionnaire in basic competency of conceiving various effects and threats against the state in maintaining Bhinneka Tunggal Ika was carried out using validity and reliability test. To find out whether or not the items of question were valid, Pearson’s product moment correlational formula was used. Meanwhile, the reliability used in this research was Alpha Cronbach. Technique of analyzing data used was a two-independent sample t test.Considering the research an average score of 86,03 experimental class is higher than he average score of 80,76 control class. Then the hypothesis testing using a two independent sample t test with t statistic > t tabel 13,560 > 1,997 at significance level of 5% means that there are difference of  civic disposition between the students in experiment and those in control classes. So that from the result it could be found that there was an effect of value clarification technique learning model on the students’ civic disposition in basic competency of conceiving various effects and threats against the state in maintaining Bhinneka Tunggal Ika in the 11th graders of SMA Negeri 1 Teras Boyolali in the School Year of 2016/2017. Keywords: Value Clarification Technique, Civic Disposition